DEVELOPING ANALYTICAL COMPETENCE OF HIGHER EDUCATION STUDENTS THROUGH ARTIFICIAL INTELLIGENCE TOOLS - Abdumalikova Gulhayo Shavkat qizi; Xolmatova Elnura Sherali qizi (TADQIQOTLAR, 2026)
Abstract This article explores the development of analytical competence among higher education students through the integration of artificial intelligence (AI) tools in the teaching and learning process. Analytical competence is considered a key component of 21st-century skills, enabling students to analyze information, evaluate problems, and make reasoned decisions. The study examines the pedagogical potential of AI-based digital platforms, adaptive learning systems, and automated analytical tasks in fostering students’  analytical  and  critical  thinking  skills.  The  findings  demonstrate  that purposeful integration of AI tools creates favorable conditions for enhancing students’ analytical competence and supports innovative practices in higher education.